2022
DOI: 10.3390/ijerph19127470
|View full text |Cite
|
Sign up to set email alerts
|

Medication Knowledge and Adherence in Type 2 Diabetes Mellitus Patients in Brunei Darussalam: A Pioneer Study in Brunei Darussalam

Abstract: Aim: The present study measured the medication knowledge and medication adherence in patients with type 2 diabetes in Brunei Darussalam. Demographic details and diabetes knowledge were also evaluated. Methods: A cross-sectional study conducted via the administration of a structured questionnaire consisting of 4 sections via a face-to-face interview. Results: A total of 118 participants were interviewed. A majority of the participants were aged 40 years or above (106, 89.8%). The mean number of total medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The present study found that participants’ diabetes knowledge is positively correlated with medication adherence (rho = 0.425, p < 0.001). Similar to the present study, AlShayban et al, Kassahun et al, and Haskani et al reported that patients with a good knowledge of diabetes had better medication adherence and, in turn, better glycemic control [ 10 , 38 , 42 ]. The present study found a weakly positive correlation between participants’ brief perception of diabetes and medication adherence (rho = 0.217, p = 0.007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study found that participants’ diabetes knowledge is positively correlated with medication adherence (rho = 0.425, p < 0.001). Similar to the present study, AlShayban et al, Kassahun et al, and Haskani et al reported that patients with a good knowledge of diabetes had better medication adherence and, in turn, better glycemic control [ 10 , 38 , 42 ]. The present study found a weakly positive correlation between participants’ brief perception of diabetes and medication adherence (rho = 0.217, p = 0.007).…”
Section: Discussionsupporting
confidence: 89%
“…Patients’ awareness of and knowledge about their chronic illness and its management are two of the essential components for their better understanding of the treatment protocols [ 10 , 11 ]. Previous studies demonstrated that in order to properly self-manage diabetes, a patient must have a thorough understanding of medications, food, exercise, home glucose monitoring, foot care, and necessary treatment changes.…”
Section: Introductionmentioning
confidence: 99%
“…If this situation is left unchecked and lasts a long time, it will cause both macrovascular and microvascular complications. The reasons for patients' not-adherence to carrying out therapy in this study were factors for forgetting to take medication, patients already feeling healthy, complex therapy regimens, and patients feeling worried about the side effects of the drugs they took for a long time [28].…”
Section: Resultsmentioning
confidence: 87%
“…Due to the high prevalence of T2DM in the sultanate, the government has been implementing several initiatives to curtail the disease prevalence. 4 The rising obesity issue among youth in Brunei also triggered alarm to nip the problem in the bud before it leads to metabolic syndromes such as DM. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Due to the high prevalence of T2DM in the sultanate, the government has been implementing several initiatives to curtail the disease prevalence. 4 The rising obesity issue among youth in Brunei also triggered alarm to nip the problem in the bud before it leads to metabolic syndromes such as DM. 5,6 These programmes use a variety of strategies, including health promotion and health education campaigns, in an effort to increase public knowledge of diabetes prevention.…”
Section: Introductionmentioning
confidence: 99%